Long‐term longitudinal changes in baseline PSA distribution and estimated prevalence of prostate cancer in male Japanese participants of population‐based PSA screening. Issue 7 (14th May 2018) - Oki, Ryo; Ito, Kazuto; Suzuki, Rie; Fujizuka, Yuji; Arai, Seiji; Miyazawa, Yoshiyuki; Sekine, Yoshitaka; Koike, Hidekazu; Matsui, Hiroshi; Shibata, Yasuhiro; Suzuki, Kazuhiro
Abstract : Japan has experienced a drastic increase in the incidence of prostate cancer (PC). To assess changes in the risk for PC, we investigated baseline prostate specific antigen (PSA) levels in first‐time screened men, across a 25‐year period. In total, 72, 654 men, aged 50–79, underwent first‐time PSA screening in Gunma prefecture between 1992 and 2016. Changes in the distribution of PSA levels were investigated, including the percentage of men with a PSA above cut‐off values and linear regression analyses comparing log10 PSA with age. The 'ultimate incidence' of PC and clinically significant PC (CSPC) were estimated using the PC risk calculator. Changes in the age‐standardized incidence rate (AIR) during this period were analyzed. The calculated coefficients of linear regression for age versus log10 PSA fluctuated during the 25‐year period, but no trend was observed. In addition, the percentage of men with a PSA above cut‐off values varied in each 5‐year period, with no specific trend. The 'risk calculator (RC)‐based AIR' of PC and CSPC were stable between 1992 and 2016. Therefore, the baseline risk for developing PC has remained unchanged in the past 25 years, in Japan. The drastic increase in the incidence of PC, beginning around 2000, may be primarily due to increased PSA screening in the country. Abstract : What's new? An increase in incidence rates of prostate cancer has alarmed researchers in Japan in recent years. Here the authors developed a prostate cancer risk calculator (RC) to estimate the RC‐based age‐standardized incidence rate based on baseline prostate‐specific antigen (PSA) recordings between 1992 and 2016. They found the local baseline risk for developing prostrate cancer to be unchanged in the past 25 years pointing to increased usage of PSA monitoring as a potential explanation for the increased cancer incidence.